Teach First organisational discourse: what are Teach First teachers really being trained for? - Elliott, Jenny (SAGE, 2018)
This paper considers the networked nature of Teach First in order to illustrate the different business, philanthropic and educational agents that have a vested interest in the organisation. It also reflects on Teach First’s strategic positioning within the ITE landscape in order to attract high calibre graduates into the teaching profession and goes on to explore Teach First’s institutional discourse and the ways in which this serves to shape the Teach First teachers’ understandings of themselves, teaching and their potential career prospects after their two year commitment on the Teach First programme. An understanding of the Teach First institutional discourse is gained through an analysis of data gathered from Teach First documentation and interviews with people working at different levels within the organisation. Critical Discourse Analysis is used to understand the ways in which this institutional discourse serves to provide a particular ideological positioning for Teach First and its teachers. It argues that such a positioning encourages them to take with them a neoliberal understanding of ways of working into influential positions within the wider network invested in Teach First.